The Reconstruction of Islamic Law from a Sociological Perspective - Henny Saida Flora; Faris Sulaiman; Amina Zahra; Adam Zayn; M. Rusdi (Insani: Jurnal Pranata Sosial Hukum Islam, 2026)
Normative authority no longer relies solely on sacred texts, but is dynamically negotiated through power relations, social practices and collective consciousness. This study aims to analyse the reconstruction of Islamic law from a sociological perspective by examining the relationship between legal norms, social dynamics, power structures and interactions between actors in the formation of legal legitimacy. This study employs a qualitative approach with a critical socio-legal design that integrates a normative analysis of Islamic law with the empirical realities of society. The findings indicate that the legitimacy of Islamic law no longer rests solely on textual authority, but is shaped through an ongoing process of negotiation between the text, the social context, and legal actors within an increasingly pluralistic and digitalised society. The novelty of this study lies in developing a framework for the reconstruction of Islamic law that integrates living law, legal pluralism, digital transformation, and an orientation towards maqāṣid al-sharī‘ah as the foundation for law that is both adaptive and transformative. These findings underscore the need for legal reform through an interdisciplinary approach, strengthening religious legal literacy, and developing a more participatory legal authority to ensure that Islamic law remains relevant in the face of social change. Nevertheless, this study still has limitations in terms of the scope of cross-contextual empirical evidence and has not yet tested the proposed reconstruction model in institutional practice. Therefore, further research needs to conduct empirical validation through comparative studies and implement the model across various legal systems and public policies.